m6A regulator-based methylation modification patterns and characterization of tumor microenvironment in acute myeloid leukemia - Xu, Zi-Jun; Wen, Xiang-Mei; Zhang, Yuan-Cui; Jin, Ye; Ma, Ji-Chun; Gu, Yu; Chen, Xin-Yi; Xia, Pei-Hui; Qian, Wei; Lin, Jiang; Qian, Jun (Frontiers in Genetics, 2022)
RNA N6-methyladenosine (m6A) is the most common and intensively studied RNA modification that critically regulates RNA metabolism, cell signaling, cell survival, and differentiation. However, the overall role of multiple m6A regulators in the tumor microenvironment (TME) has not yet been fully elucidated in acute myeloid leukemia (AML). In our study, we explored the genetic and transcriptional alterations of 23 m6A regulators in AML patients. Three distinct molecular subtypes were identified and associated with prognosis, patient clinicopathological features, as well as TME characteristics. The TME characterization revealed that m6A patterns were highly connected with metabolic pathways such as biosynthesis of unsaturated fatty acids, cysteine and methionine metabolism, and citrate cycle TCA cycle. Then, based on the differentially expressed genes (DEGs) related to m6A molecular subtypes, our study categorized the entire cohort into three m6A gene clusters. Furthermore, we constructed the m6Ascore for quantification of the m6A modification pattern of individual AML patients. It was found that the tumor-infiltrating lymphocyte cells (TILs) closely correlated with the three m6A clusters, three m6A gene clusters, and m6Ascore. And many biological processes were involved, including glycogen degradation, drug metabolism by cytochrome P450, pyruvate metabolism, and so on. Our comprehensive analysis of m6A regulators in AML demonstrated their potential roles in the clinicopathological features, prognosis, tumor microenvironment, and particularly metabolic pathways. These findings may improve our understanding of m6A regulators in AML and offer new perspectives on the assessment of prognosis and the development of anticancer strategy.